Tetanus Following Root Canal Surgery - Ahmed, Hafizuddin (KYAMC Journal, 2013)
2400 years ago Hippocrates recognised Tetanus as a dreadful disease.It is caused by a straight slender gram positive anaerobic rod-Clostridium Tetani, the toxin of which interferes with acetylecholine/cholinesterase balance at peripheral motor end plate of central nervous system causing sustained tonic spasm. Children are routinely immunized these days everywhere against Diptheria,Pertisis,Tetanus,Poliomyelitis etc.But this does not apply with aged people who were not routinely immunized during their infancy making them vulnerable to these diseases including Tetanus. Majority of Tetanus cases follow wounds(war,accidents,post-operative) contaminated with soil,manure or other external sources.Following is a rare case where tetanus occured without so called wound i.e.Clostrdium Tetani infected pulp space in the root of the tooth following root canal surgery.As the pulp space becomes a closed chamber after filling it with inert material in R.C.T. so anaerobic infection can occur here as it occured in this case of 42 year old female school teacher.All wounds however trival from whatever cause should be considered tetanus prone. DOI: http://dx.doi.org/10.3329/kyamcj.v3i1.13663 KYAMC Journal Vol. 3, No.-1, June 2012 pp.265-268